2013
DOI: 10.1167/iovs.12-10014
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone, a Blocker of Glucocorticoid Receptors, Promotes Photoreceptor Death

Abstract: PURPOSE. Glucocorticoids are best known by their protective effect on retinal photoreceptor damage. However, they could also be involved in photoreceptor homeostasis under basal, nonstressful conditions. Therefore, we aimed to study glucocorticoid-induced changes of survival-related molecules in male mice retinas under standard illumination conditions (12 hours light, 60 lux/12 h dark).METHODS. Male Balb-c mice were injected with dexamethasone (DEX), a selective glucocorticoid receptor a (GRa) agonist, its ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Response to glucocorticoid treatment in the eye implies a natural role for glucocorticoid signaling in the eye. Furthermore, by using rodent models, it has been shown that glucocorticoids confer protection in photoreceptors in the retina by preventing their apoptosis [53, 54]. …”
Section: The Role Of Glucocorticoids In Health and Diseasementioning
confidence: 99%
“…Response to glucocorticoid treatment in the eye implies a natural role for glucocorticoid signaling in the eye. Furthermore, by using rodent models, it has been shown that glucocorticoids confer protection in photoreceptors in the retina by preventing their apoptosis [53, 54]. …”
Section: The Role Of Glucocorticoids In Health and Diseasementioning
confidence: 99%
“…In contrast, MR overexpression inhibited apoptosis and promoted survival of embryonic stem cell-derived neurons [ 84 ]. Unlike in other brain regions, glucocorticoids play a critical role in retinal photoreceptor survival, whereas mifepristone, which has the capacity to block glucocorticoid receptors, promotes photoreceptor death [ 85 ]. Furthermore, an MR agonist aldosterone appeared to be a critical mediator of retinal ganglion cell loss that was independent of elevated intraocular pressure [ 86 ].…”
Section: Interactions Of Apoptosis and Autophagy With Steroid And mentioning
confidence: 99%
“…Studies in neurons, on the other hand, have not primarily focused on the links between H2AX and apoptosis. They aimed, instead, to assess the response of isolated cells or the intact brain to several DNA-damaging agents of heterogeneous nature (e.g., hydrogen peroxide [ 10 ] and mifepristone [ 11 ]) that have been reported to induce γH2AX with [ 11 ] or without [ 10 ] the concomitant activation of CASP3.…”
Section: Introductionmentioning
confidence: 99%